‘You are what you share to wear’ Self-identity formation through fashion in the age of Sharing economy - Aziz, Umema (2020)
The need for sustainable business models for fashion has given a rise to fashion sharing economy. Research has shown that possessions, such as fashion, are heavily interconnected with self-identity formation. This study aims to determine the self-identities young female consumers form and wish to signal through the use of preloved and/or rental fashion. Building on the extant literature, it asks: how do people want to be perceived by others for their collaborative fashion consumption? It also identifies motivations behind the participation of young females consumers in the sharing economy of fashion. A literature-driven conceptual framework was introduced in this research to understand the motivations for partaking in sharing economy. The study adopted a qualitative, in-depth interview technique to examine the self-identity construct in fashion sharing and builds on to the conceptual framework using the findings. Analysis of the data revealed that consumers want to construct four types of self-identities when it comes to fashion sharing: individualistic, conscious consumer, smart spender, and fashionable. It was found that consumers have an overlap of motivations to participate in the sharing economy. Despite the widely addressed environmental concerns surrounding fast fashion, utilitarian and hedonic motivations took precedence for majority of respondents. The study concluded that fashion retailers need to take a holistic approach towards being prosocial in their practices, and position their brands in a way that caters to varying motivations and self-identities of consumers.